Prioritization of strategies for a sustainable regional transportation infrastructure by hybrid spherical fuzzy group decision-making approach - Bouraima, Mouhamed Bayane; Qiu, Yanjun; Ayyildiz, Ertugrul; Yildiz, Aslihan (SPRINGER LONDON LTD, 2023)
The East African Community, inspired by successful trading blocs, has already begun major transportation strategic plans that will necessarily require large investments. Additionally, significant efforts have been made to harmonize regional transportation legislation and regulations. However, some challenges that may arise in developing such a sustainable regional transportation infrastructure should be carefully determined. In this study, a spherical fuzzy multi-criteria decision-making method is proposed. Ten criteria characterizing the challenges in the regional transportation infrastructure problem have been identified as a result of the pertaining reviewed literature and expert opinions. These criteria were used to prioritize seven strategies for sustainable regional transportation infrastructure. To address complex group decision-making issues, this study presents the integration of Weighted Aggregated Sum Product Assessment (WASPAS) with Step-Wise Weight Assessment Ratio Analysis (SWARA) in a spherical fuzzy (SF) environment. The weight and importance levels of criteria are evaluated using SF-SWARA. SF-WASPAS is then used to prioritize the strategies based on the SF-SWARA-weighted criteria. To assess the effectiveness of the proposed methodology, a sensitivity analysis is carried out, revealing that research and development (S7) and adequate institutional and regulatory framework (S4) are the most appropriate strategies for dealing with these challenges, respectively. The study offers a novel approach for regional political leaders who aim to promote progressive policy, regulatory, and economic frameworks, along with a strong human and institutional capacity for collaborative research, technology, and innovation.
Keywords: Transportation infrastructure; WASPAS; SWARA; Spherical fuzzy sets; LOCATION SELECTION; WASPAS METHOD; SETS; PERSPECTIVE; VEHICLE; AFRICA; Computer Science